Implementasi Pendidikan Kewirausahaan Dalam Menumbuhkan Minat Berwirausaha Siswa Kelas XI Di SMK Negeri 3 Muna - Murni Nia; Nanik Hindaryatiningsih; Lisna Wati; Jumatin Jumatin; Muhammad Juwantho Lewa (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to describe the implementation of creativity in fostering entrepreneurial interest among Grade XI students at SMK Negeri 3 Muna. Creativity is one of the core values of entrepreneurship education, realized through the KIK (Creativity, Innovation, and Entrepreneurship) subject with a focus on practical bag-making using traditional Muna woven fabric. The study employed a descriptive qualitative approach. Research subjects consisted of the Vice Principal for Curriculum, KIK subject teachers, and Grade XI Fashion Design students. Data were collected through participatory observation, in-depth interviews, and documentation studies. Data analysis followed the Miles and Huberman model through data reduction, data display, and conclusion drawing, with validity tested through source and technique triangulation. The results show that creativity is implemented through four concrete forms: (1) freedom of expression in product design and sewing; (2) creative idea development based on the local potential of Muna woven fabric; (3) creative product packaging with student-branded labels; and (4) creative marketing through bazaars and exhibitions. Creativity systematically applied in KIK learning has proven to foster students' entrepreneurial interest, evidenced by increased enthusiasm, courage in marketing products, self-confidence, and the emergence of desire to start independent businesses.